Chemical Heritage Foundation Innovation Day: Gordon E. Moore Award presentation - Chemical Heritage Foundation (2004)
This video captures the first ever presentation of the Society of Chemical Industry's (SCI) Gordon E. Moore Medal for early-career success in innovation, given to George Barclay of Rohm and Haas for his work in creating new polymers for deep ultra-violet photoresists used in semiconductors. Raj Gupta introduces SCI Awards Committee chair Jim Elder, who introduces Gordon Moore, who then presents the award to George Barclay. Jeffrey Lipton introduces Pennsylvania Governor Ed Rendell who speaks on the importance of chemistry to the industry, environment, and economic future of Pennsylvania.
Keywords: Chemical Heritage Foundation; Society of Chemical Industry (Great Britain). American Section; Chemistry--Awards; Chemical industry; Semiconductor industry; Moore, Gordon E., 1929-2023